1978
DOI: 10.1007/bf02552045
|View full text |Cite
|
Sign up to set email alerts
|

The early radiologic findings in the adult chest after cardiopulmonary bypass surgery

Abstract: Postoperative chest radiographs of 70 adults who had undergone cardiopulmonary bypass surgery were evaluated. The distribution of pulmonary collapse/consolidation and pleural effusions, and the pattern of radiopacities related to drainage tubes were considered. Radiologic manifestations related to sternotomy were noted. Cases with a recorded postoperative blood loss of more than 280 ml/hour and/or an increase in mediastinal width of more than 70% had massive mediastinal hemorrhage that required reoperation. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The relatively low prevalence (4%) of the midsternal stripe sign in the control group in our series is similar to the results reported by Escovitz et al [8] but is significantly lower than the prevalences reported in other published series [4,9,12] (Table 1). The reason for this difference is unclear but may reflect variations in radiographic technique [10] among various institutions or in observer thresholds for the detection of thin stripes.…”
Section: Discussionsupporting
confidence: 87%
“…The relatively low prevalence (4%) of the midsternal stripe sign in the control group in our series is similar to the results reported by Escovitz et al [8] but is significantly lower than the prevalences reported in other published series [4,9,12] (Table 1). The reason for this difference is unclear but may reflect variations in radiographic technique [10] among various institutions or in observer thresholds for the detection of thin stripes.…”
Section: Discussionsupporting
confidence: 87%
“…During the early postoperative period after HLT, cardiothoracic surgeons commonly encounter various radiological findings on follow‐up chest radiographs. Fortunately, most early postoperative radiographic changes are clinically insignificant findings related to surgical procedures, such as pleural effusion, lower lobe atelectasis, pneumothorax, and mediastinal widening 4–6 . In the present case, radiographic density in the left lower lung field was initially considered postoperative atelectasis because it is a well‐known postoperative radiographic abnormality; lower lobar atelectasis is frequently located in the medial portion and may persist up to the 3rd postoperative week 6 .…”
Section: Discussionmentioning
confidence: 78%
“…The early complications of HLT include primary graft failure, bleeding, acute rejection, infection, and anastomotic pitfalls 2,3 . In addition, patients with HLT have various findings on serial follow‐up chest radiographs in the early postoperative period, usually reflecting surgical procedures and of little clinical significance 4–6 . However, certain persistent radiological findings can provide important clues for detecting unusual complications of HLT, such as lung herniation 7,8 .…”
Section: Introductionmentioning
confidence: 99%